Long-term outcome of severe acute kidney injury survivors followed by nephrologists in a developing country - Ponce, Daniela [UNESP]; Dias, Dayana Bitencourt [UNESP]; Nascimento, Ginivaldo Ribeiro [UNESP]; Silveira, Liciana Vaz De Arruda [UNESP]; Balbi, André Luís [UNESP] (Wiley, 2016)
Aim This study aimed to evaluate the long-term outcome of patients after a severe episode of acute kidney injury (AKI) on survival and progression to chronic kidney disease (CKD) and to identify risk factors associated with these outcomes. Methods We performed a prospective study that evaluated the long-term outcome of 509 AKI stage 3 patients who were followed by nephrologists in a Brazilian University Hospital from 2004 to 2013. Results Age was 60.2 years (47.5-71) and the follow-up time was 25 months (12-44). The late mortality was 38.1% and age (HR 2.89, 95%CI=1.88 to 4.46, P < 0.0001), diabetes (HR 1.46, 95%CI=1 0.02 to 2.16, P < 0.047), liver disease (HR 2.95, 95%CI=1.19 to 7.3, P = 0.02) and creatinine (Cr) at the time of hospital discharge (HR 1.21, 95%CI=1.04 to 1.41, P = 0.01) were associated with poor long-term survival. At the moment of hospital discharge, 52.1% of patients had complete recovery of renal function, 39.7% had partial recovery and 8.3% had not recovered renal function. After 36 months, 43.5% of patients progressed to CKD, and 5.3% needed for chronic dialysis. Factors associated with progression to CKD were age (HR 1.02, 95%CI=1.008 to 1.035, P = 0.009), CKD (HR 1.05 95% CI=1.007 to 1.09, P = 0.04), diabetes (HR 1.12, CI 1.008-1.035, P = 0.009) and number of AKI episodes (HR 1.65, 95%CI=1.19 to 2.2, P = 0.0023). Conclusion This study showed that AKI patients have high mortality after hospital discharge and age, diabetes, liver disease, and Cr value at the time of discharge were factors associated with long-term mortality. The risk factors for this progression to CKD were age, the presence of diabetes and the number of AKI episodes.
Keywords: acute kidney injury; long-term; progression to chronic kidney disease; survival